Delphi-based Spanish consensus on the use of long-acting growth hormone in pediatric growth hormone deficiency: recommendations from the ConverGHe Working Group - Castro-Feijóo, Lidia; Labarta-Aizpún, José-Ignacio; Ramon-Krauel, Marta; Primiano, Diana; Yeste Fernández, Diego; González Casado, Isabel (Frontiers in Endocrinology, 2025)
BackgroundLong-acting growth hormone (LAGH) formulations have emerged as an alternative to daily recombinant human growth hormone (rhGH) in pediatric growth hormone deficiency (GHD). Although evidence from meta-analyses and randomized trials supports their efficacy and safety, real-life data are still lacking, and therefore clinical guidance on their implementation remains limited.ObjectiveTo develop expert-based recommendations for the clinical use of LAGH in pediatric GHD within Spain.MethodsA two-round Delphi approach was used. Based on a literature review, a scientific committee comprised of pediatric endocrinologists developed a questionnaire structured into three domains: (1) Main benefits of LAGH vs. daily rhGH; (2) Candidate profiles for LAGH therapy; and (3) Considerations for initiating LAGH and treatment monitoring. Panelists rated their level of agreement with each questionnaire statement on a 9-point Likert scale. Consensus was defined as ≥66.67% of responses on the same tertile as the median, labelled as disagreement on scores of 1–3, intermediate on scores of 4–6, and agreement on scores 7–9. Statements that did not reach consensus were reformulated and re-evaluated in round 2.ResultsAfter two rounds, all statements achieved consensus on agreement. Specifically, consensus was reached on 92% of the statements in round 1 and three revised items related to insulin-like growth factor-1 (IGF-1), pharmacokinetics and dose adjustment criteria, as well as the use of LAGH in patients at risk of hypoglycemia, achieved consensus in round 2. The recommendations emphasize the similar efficacy and safety of LAGH compared to rhGH, raising its special interest in cases of poor adherence to daily formulations (e.g. adolescents, injection-related anxiety, multiple comorbid treatments or complex family circumstances), although LAGH should also be considered in other settings in a patient-centered approach. In addition, they provide guidance on key issues related to adequate dose initiation and titration, as well as therapeutic monitoring.ConclusionThis is the first Delphi consensus to provide national-level guidance on integrating LAGH into pediatric GHD care, offering practical recommendations based on current evidence and national expert opinion. Future long-term real-world experience will contribute to address questions regarding long-term efficacy and safety, and practice-related points such as indication and monitoring.